Differential Proteomic Analysis of Lactic Acid Bacteria—Escherichia coli O157:H7 Interaction and Its Contribution to Bioprotection Strategies in Meat - Orihuel, Alejandra; Terán, Lucrecia; Renaut, Jenny; Vignolo, Graciela M.; De Almeida, André M.; Saavedra, María L.; Fadda, Silvina (Frontiers in Microbiology, 2018)
Human infection by Enterohemorrhagic Escherichia (E.) coli (EHEC) occurs through the ingestion of contaminated foods such as milk, vegetable products, water-based drinks and particularly minced meats. Indeed EHEC is a pathogen that threatens public health and meat industry. The potential of different Lactic Acid Bacteria (LAB) strains to control EHEC in a meat-based medium was evaluated by using a simple and rapid method and by analyzing the growth kinetics of co-cultures (LAB-EHEC) in a meat-based medium. The activity of LAB towards EHEC in co-cultures showed variable inhibitory effect. Although, LAB were able to control EHEC, neither the produced acid nor bacteriocins were responsible of the inhibition. The bacteriocinogenic Enteroccus (Ent.) mundtii CRL35 presented one of the highest inhibition activities. A proteomic approach was used to evaluate bacterial interaction and antagonistic mechanisms between Ent. mundtii and EHEC. Physiological observations, such as growth kinetics, acidification ability and EHEC inhibitory potential were supported by the proteomic results, demonstrating significant differences in protein expression in LAB: i) due to the presence of the pathogen and ii) according to the growth phase analyzed. Most of the identified proteins belonged to carbohydrate/amino acid metabolism, energy production, transcription/translation and cell division. These results contribute to the knowledge of competition strategies used by Ent. mundtii during its co-culture with EHEC setting new perspectives for the use of LAB to control this pathogen in meat.